2005
DOI: 10.1103/physrevb.72.134404
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance enhancement in epitaxial magnetite films grown on vicinal substrates

Abstract: The magnetoresistance ͑MR͒ behavior of epitaxial magnetite Fe 3 O 4 grown on low-vicinal ͑small miscut͒ and high-vicinal ͑large miscut͒ MgO substrates is compared. Magnetization measurements on Fe 3 O 4 films on high-vicinal substrates showed reduced magnetic moment as compared with the films grown on low-vicinal MgO, which correlates well with the expected reduction in magnetic moment due to step edge induced additional antiphase boundaries ͑APBs͒ with out-of-plane shift vectors. The MR is significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
82
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 40 publications
(56 reference statements)
6
82
0
Order By: Relevance
“…11,12 Magneto-transport studies in epitaxial magnetite films are mostly focused on the influence of APBs, disorder and strain. In a recent study, 13 we have shown that if these nano-scale defects in Fe 3 O 4 films are manipulated in an ordered fashion one can attain a sizable magnetoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Magneto-transport studies in epitaxial magnetite films are mostly focused on the influence of APBs, disorder and strain. In a recent study, 13 we have shown that if these nano-scale defects in Fe 3 O 4 films are manipulated in an ordered fashion one can attain a sizable magnetoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 The presence of anti-phase boundary defects in Fe 3 O 4 contribute to its unusual magnetic and transport properties, such as the magnetization non-saturation even at very high field, 30,31 the super-paramagnetic behavior in Fe 3 O 4 films, 32,33 and a greater MR response across the AF-APBs. [34][35][36] On the other hand, in polycrystalline Fe 3 O 4 thin films, interesting properties such as magnetic-transport, 37 spin-injection, 38 and charge ordering 39,40 have also been investigated and discussed. Therefore, it is worth investigating the magnetic properties of stepped epitaxial Fe 3 O 4 films produced on large miscut angle vicinal MgO substrates, as a high density APBs is expected along the step edges.…”
mentioning
confidence: 99%
“…Details of the growth conditions used for Fe 3 O 4 layers are given elsewhere. 12 The NiO ͑15 nm͒ epilayer was deposited at a substrate temperature of 600°C with an oxygen partial pressure 5 ϫ 10 −6 Torr. After the NiO growth, the sample was cooled to 250°C and a 10 nm film of Fe 3 O 4 was grown to serve as the bottom FM layer.…”
mentioning
confidence: 99%